South Africa’s Other Whites - Jaster, Robert Scott. author. aut Link
XIV, 151 p.
Keywords: The voices speaking here represent an extraordinary group of South Africans: those whites - a minority within a minority - who have been struggling against the injustices of apartheid and working in separate ways to prepare their countrymen, black and white, for a just and democratic post-apartheid society. This book captures their stories at a critical time, when apartheid is being dismantled but the structure of the new South Africa has yet to be determined.